Intervención psicoterapéutica en pacientes de 50 a 65 años de edad, en etapa inicial del tratamiento de hemodiálisis del Hospital Regional Isidro Ayora de la ciudad de Loja en el periodo agosto 2013 – enero 2014. - Vicente Macas, María Elisa (2014)
The Chronic Renal Insufficiency can be defined as the situation where a global failure of all kidney function occurs, hindering vital regulatory activities of the internal environment. Taking as origin alterations in kidney function : purification, regulatory and endocrine-metabolic, resulting in the retention of toxic metabolic products and alteration in the volume, and solute concentration in the acid -base balance various body compartments, endangering the patient's life, being essential for the substitution of these functions is established. Patients suffering from this disease received basic treatment as hemodialysis, which is a complex procedure that generates emotional and behavioral changes in the lifestyle of the individual. The present study aimed to perform psychotherapeutic intervention for patients 50 to 65 years, 27 patients underwent initial treatment stage Hemodialysis Isidro Ayora Hospital Regional City Loja. Questionnaire international examination of IPDE personality disorders - For the development of this research study, which lasted 6 months esteem, psychological reagents (Beck Depression Inventory, Anxiety Scale Hamilton and International Personality Disorder Examination Questionnaire was applied MODULE DSM -IV) and concluded that the most prevalent psychopathology are: Depression and Anxiety, the same that are triggered by multiple problems and changes at the individual, family, marital conflict, social and economic. Psychotherapeutic intervention plan was formulated with integrative approach; the main objective of this psychotherapeutic technique is to provide psychological care to patients with chronic renal failure by reducing symptoms and emotional disturbances. The therapeutic process we perform through three strategies: research, planning and implementation of techniques. By this it was possible to obtain the clinical diagnosis, fix targets and therapeutic plan with the various psychological techniques used. KEYWORDS: The Chronic Renal Insufficiency, Psychotherapeutic Intervention, Depression, Anxiety.